Pengembangan E-book Menggunakan Flipbook Pada Muatan Ilmu Pengetahuan Alam Materi Perpindahan Panas Dan Kalor - Hidayat, Nada Syifa; Mulyawati, Yuli; Suchyadi, Yudhie (Universitas Muhammadiyah Bangka Belitung, 2024)
The rapid development of technology has significantly impacted various fields, including education. Innovations in educational technology have become crucial to keep the learning process relevant and engaging for students. This study aims to develop and test the feasibility of e-book-based teaching materials using flipbook for the subject of heat transfer and heat in the Natural Science course for Grade V students. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Initial data were obtained through observation and interviews with class teachers as well as questionnaires to students. The results of the study indicate that the use of flipbook-based e-books can increase students' interest and understanding of the subject matter. Validation by experts in language, media, and content shows that this e-book is highly feasible for use in teaching, with each expert's feasibility score meeting the criteria for excellence. Limited implementation with 25 Grade V students at SD YPI HM Asman showed a positive response with an assessment percentage of 90%. Therefore, this flipbook-based e-book is considered highly feasible and effective for use in Natural Science teaching, providing more interesting variations and interactions, and helping students better understand the material.